Estimating hunting prevalence and reliance on wild meat in Cambodia's Eastern Plains. Issue 6 (23rd November 2021) - Ibbett, Harriet; Keane, Aidan; Dobson, Andrew D.M.; Griffin, Olly; Travers, Henry; Milner-Gulland, E.J.
Abstract: Hunting is a primary driver of biodiversity loss across South-east Asia. Within Cambodia, the use of wire snares to capture wildlife is a severe threat in protected areas but there have been few studies of the behaviour of hunters from local communities. Here, we combine the unmatched count technique with direct questioning to estimate the prevalence of hunting behaviours and wildlife consumption amongst 705 households living within Keo Seima Wildlife Sanctuary, Cambodia. We assessed respondents' knowledge of rules, and their perceptions of patrols responsible for enforcing rules. Estimates of hunting behaviour were variable: results from the unmatched count technique were inconclusive, and direct questioning revealed 9% of households hunted, and 20% set snares around farms to prevent wildlife eating crops. Hunting with domestic dogs was the method most commonly used to catch wildlife (87% of households owned dogs). Wild meat was consumed by 84% of households, and was most frequently bought or caught, but also gifted. We detected a high awareness of conservation rules, but low awareness of punishments and penalties, with wildlife depletion, rather than the risk of being caught by patrols, causing the greatest reduction in hunting. Our findings demonstrate the challenges associated with reliably estimating rule-breaking behaviour and highlight the need to incorporate careful triangulation into study design.